On the determination of the temperature distribution within the color conversion elements of phosphor converted LEDs - Nemitz, Wolfgang (Sci Rep, 2017)
We present an iterative optical and thermal simulation procedure which enables the determination of the temperature distribution in the phosphor layer of a phosphor converted LED with good accuracy. Using the simulation both the highest phosphor temperatures, which are mostly relevant to material degradation as well as the temperatures of those phosphor particles which mainly contribute to converted light emission can be determined. We compare the simulations with experimental studies on the phosphor temperature. While infrared thermography only gives information on the phosphor layer surface temperature, phosphor thermometry provides temperature data on the volume temperature of the phosphor layer relevant to color conversion.